Information communication technology: reform of organisational crisis management during natural disasters. (19th May 2008) - McDonald, Sean M.; Sinha, Ranu
Based on the trends within the last century of relative increases in global threats in the form of terrorist attacks, natural disasters, health pandemics and chemical and biological threats, it is imperative to test the robustness of current government crisis management capabilities. In conjunction with the growth in asymmetric threats, there has been a digital revolution in technology in relation to disaster response. Information Communication Technology (ICT) tools have key properties that are vital for traditionally 'inflexible' organisations managing modern risks and vulnerabilities. Lessons from past cases of major natural disasters in the UK and Turkey illustrate specific areas where emergency response agencies continuously exhibit weaknesses during response operations. Some of these limitations can be specifically targeted by means of technological solutions, while others need fundamental change to organisational design and policy making.